Source Apportionment of Carcinogenic Polycyclic Aromatic Hydrocarbons in Urban Road Dust (Journal of Pure and Applied Sciences (Science Forum), 2025)
This study assessed and compared the concentrations of polycyclic aromatic hydrocarbons (PAHs) in road dust collected from various zones within Durban City, South Africa, including the city centre, residential areas, and industrial districts. The investigation aimed not only to quantify PAH levels but also to identify their likely sources and assess potential health risks. Measured concentrations of total PAHs varied across the different land-use areas: from 77 to 1488.85 µg·kg⁻¹ in the city centre, up to 2108 µg·kg⁻¹ in residential areas, and between 138 and 1409 µg·kg⁻¹ in industrial zones. These variations reflect differing emission sources and traffic intensities across the city. To determine the origin of PAHs, several molecular diagnostic ratios were calculated, including phenanthrene/anthracene (0.03, 0.34, and 0.41), benz[a]anthracene/chrysene (0.99 and 0.85), benzo[b]fluoranthene/benzo[k]fluoranthene (1.51 and 1.53), and benzo[a]pyrene/benzo[e]pyrene (0.98 and 0.92). These ratios, alongside results from principal component analysis (PCA), indicated that the dominant sources of PAHs were related to the incomplete combustion of petroleum products—primarily vehicular emissions from gasoline and diesel engines. Furthermore, the study employed toxicity equivalency factors (TEFs) to estimate the carcinogenic potential of individual PAH compounds. Health risk assessments were conducted using the hazard index (HI) and incremental lifetime cancer risk (ILCR) metrics. Results indicated that, while PAHs were present in varying concentrations, the associated health risks—both noncarcinogenic and carcinogenic—were within acceptable limits, suggesting that road dust PAHs in Durban do not currently pose significant health concerns for the urban population.